Train of the White Pass & Yukon Railway on Broadway, Skagway, Alaska, October 3, 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Broadway, Skaguay, Alaska. Oct. 3, 1898" Original image in Hegg Album 3, page 40.